Lígua, discurso e prosódia: investigar o uso da vírgula érestrito? Vírgula! - Soncin, Geovana Carina Neris [UNESP] (2014)
This work proposes to consider the prosodic-enunciative functioning as constitutive of comma uses. From the assumption of prosody organizes all language production, it is defended that prosody constitutes the writing, because it manifests as a significant component that organizes the comma uses. Then, simultaneously, prosody has a role on form and on meaning in the linguistic and discursive plans. This defense is based, firstly, on the approach according to which prosody is not an acessory aspect in the linguistic system, but, unlike, it is an important part of it; secondly, in the formulation that prosody is the material base for the expressive intonation of the utterance and, because of that, it shows the dialogical process of meaning construction when gives evidences about the expressivity of the subjects and positions taken by them; finally, in the assumption that the writing is an heterogeneous mode of enunciation, because it is constituted by social practices from orality and literacy. Methodologically, the conventional and unconventional comma uses are identified from prosodic unities. Specially based on the idea of prosodic boundary, these unities organize language facts (in the syntactic, semantic and pragmatic plans) and discursive facts (as affiliations to certain ways of saying) that are stated in the analysed texts’ writing enunciation. These texts were written in a school by students from the last grade of basic education. On account of this thesis deals with conventional and unconventional comma uses, showing their linguistic and discursive regularities, the rules that prescribe the comma uses are also an object of analysis. It is defended that the rules need to be relativized to be considered the heterogeneity of language, discourse and ...